INFLUENCE OF BRUCELLA ABORTUS I-206 THERMOEXTRACTS IN L- AND S-FORM ON MORPHOFUNCTIONAL STATE OF WHITE MICE ADRENAL GLANDS - V. I. Dubrovina; T. P. Starovoitova; S. A. Vityazeva; N. L. Barannikova; T. A. Ivanova; T. T. Shkaruba; S. V. Balakhonov (Acta Biomedica Scientifica, 2018)
Live vaccines are used for specific brucellosis prophylaxis in the Russian Federation. These vaccines in addition to a number of  positive properties have some limitations including high  agglutinogenicity, reactogenicity, sensitizing activity. In this  connection, the development of subunit vaccines without adverse  reactions is a perspective direction in modern vaccinology. Complex  morphological research of the adrenal glands and comparative  analysis of peripheral blood (leukogram, leukocytic index and index  of allergization) of white mice immunized with thermoextracts (ТE)  of Brucella abortus I-206 in L- and S-form and inactivated vaccine B.  abortus 19 ВА were conducted. It was shown that ТE unlike B.  abortus 19 ВА caused minor alterations in peripheral blood of the  experimental animals in early periods of observation (increase of allergization index, changes in leukogram) with the subsequent  levelling to the values in control. Expositions of the adrenal gland  zoning were determined and cellular structure was estimated in  consideration of morphometry. Changes in architectonics of the mice  organ immunized with B. abortus 19 ВА were revealed. These alterations could indicate the stress-reaction development. In  case of ТE application the given changes were insignificant and were  developed in early periods. The revealed morphological changes in  adrenal glands of laboratory animals permit to prove the necessity of  realization the further experimental researches to ТE application  as the components for development of a subcellular brucellosis vaccine.